2017
DOI: 10.1002/ccd.27035
|View full text |Cite
|
Sign up to set email alerts
|

Rotational atherectomy in the subadventitial space to allow safe and successful chronic total occlusion recanalization: Pushing the limit further

Abstract: Dissection and re-entry (DR) techniques have played a key role in the increase of success rates of chronic total occlusion (CTO) recanalization. DR usually allows wiring complex occlusions, even in case of important calcification. In extreme cases, such as in balloon failure-to-cross, rotational atherectomy (RA) might be decisive. However, according to experts' recommendations, RA should not be performed in dissection planes because of the high risk of perforation and further extending the dissection, so that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Inability to cross through fenestrations can result from two mechanisms: (a) presence of fibrocalcific tissue at the reentry site, which can in principle be overcome using a higher tip‐load polymer‐jacketed guidewire (such as Pilot 200 or Gladius) or cutting balloon dilatation; or (b) wrong guidewire tip shape, which should be corrected creating a 2‐mm, 45° bend. Finally, the presence of a large, compliant subintimal hematoma (possibly arising from multiple previous failed AFR attempts) will hinder further fenestration attempts, since the subintimal space is capable of stretching to a great extent, 10,14 thus accommodating further balloon dilatations. In such cases, intravascular ultrasound interrogation can provide invaluable information on the optimal site for reentry (where the hematoma is smaller and the true lumen is not surrounded by thick fibrocalcific tissue).…”
Section: Discussionmentioning
confidence: 99%
“…Inability to cross through fenestrations can result from two mechanisms: (a) presence of fibrocalcific tissue at the reentry site, which can in principle be overcome using a higher tip‐load polymer‐jacketed guidewire (such as Pilot 200 or Gladius) or cutting balloon dilatation; or (b) wrong guidewire tip shape, which should be corrected creating a 2‐mm, 45° bend. Finally, the presence of a large, compliant subintimal hematoma (possibly arising from multiple previous failed AFR attempts) will hinder further fenestration attempts, since the subintimal space is capable of stretching to a great extent, 10,14 thus accommodating further balloon dilatations. In such cases, intravascular ultrasound interrogation can provide invaluable information on the optimal site for reentry (where the hematoma is smaller and the true lumen is not surrounded by thick fibrocalcific tissue).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is recommended to perform this technique only if other alternatives are not available. In general, the use of RA in subadventitial space should be discouraged due to a high risk of vessel wall rupture and perforation; however as reported previously the mentioned complication could be overcome by under sizing the burr (1.25 mm is preferred) and by avoiding high rotational speed (160,000–180,000 rpm are the recommended). It should be mentioned that a similar report was described by Kaneko et al but just in antegrade CTO PCI with the older version of Rotablator.…”
Section: Discussionmentioning
confidence: 93%
“…Second, as described by Capretti et al, small-sized burrs (preferably starting from a 1.25 mm burr) with a pecking motion at conventional speeds (160 000-180 000 rpm) are recommended to reduce the risk of perforation. 19 Third, membrane-covered stents and pericardiocentesis equipment should be readily available in cases of severe perforation, but the use of a prophylactic temporary pacemaker is not indispensable. Last but not least, performance of the entire process by an experienced operator is still necessary and desirable.…”
Section: Discussionmentioning
confidence: 99%
“…13 In fact, with the increasing experience of surgeons, several studies have indicated that RA can be successfully applied in various off-label indications. 18,19 Although the effectiveness of RA in CTO has been demonstrated, the safety remains controversial, especially in retrograde CTO-PCI. Data on the feasibility of RA in retrograde CTO-PCI are based only on case reports.…”
Section: Discussionmentioning
confidence: 99%